2022
DOI: 10.3390/microorganisms10010183
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Stubborn Disease: Current Insights on an Enigmatic Problem Prevailing in Citrus Orchards

Abstract: Citrus stubborn was initially observed in California in 1915 and was later proven as a graft-transmissible disease in 1942. In the field, diseased citrus trees have compressed and stunted appearances, and yield poor-quality fruits with little market value. The disease is caused by Spiroplasma citri, a phloem-restricted pathogenic mollicute, which belongs to the Spiroplasmataceae family (Mollicutes). S. citri has the largest genome of any Mollicutes investigated, with a genome size of roughly 1780 Kbp. It is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Quantitative real-time PCR is of great interest in quantifying the titer of viruses in the early stages of the disease [13]. The incidence rate obtained in our analysis (76%) can be explained by the sensitivity of Sour orange to CEVd on the one hand and to the age of the orchards on the other hand because according to Sagouti [14], the symptoms of the Exocortis disease are favored by the susceptibility of the attacked plant, the nature of the strain of the CEVd (strong or weak) and the ambient conditions for the replication of the viroid [14]. In conclusion, the successful CEVd detection in citrus samples by real-time PCR is one approach of the best disease management practices providing sensitive, reliable and affordable detection assay for pathogen surveys in orchards [15].…”
Section: Resultsmentioning
confidence: 64%
“…Quantitative real-time PCR is of great interest in quantifying the titer of viruses in the early stages of the disease [13]. The incidence rate obtained in our analysis (76%) can be explained by the sensitivity of Sour orange to CEVd on the one hand and to the age of the orchards on the other hand because according to Sagouti [14], the symptoms of the Exocortis disease are favored by the susceptibility of the attacked plant, the nature of the strain of the CEVd (strong or weak) and the ambient conditions for the replication of the viroid [14]. In conclusion, the successful CEVd detection in citrus samples by real-time PCR is one approach of the best disease management practices providing sensitive, reliable and affordable detection assay for pathogen surveys in orchards [15].…”
Section: Resultsmentioning
confidence: 64%
“…Additionally, this test allowed for the identification of positive samples among those falling into the DAS-ELISA group of negative samples; 28% of the samples tested yielded positive results. This might mostly be explained by the fact that ELISA is known to have a detection sensitivity lower than DNA-based methods [ 18 , 30 , 34 ] due to the low titers of the pathogen or because of its uneven distribution in the plant and low titers in diseased trees, as well as considerable seasonal fluctuations [ 7 ]. The increased sensitivity of qPCR has additional value for the early detection of the disease agent [ 21 , 24 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The causal agent of CSD is Spiroplasma citri , a helical motile, wall-less, and cultivable microorganism that belongs to the class Mollicutes [ 3 ]. The pathogen is phloem limited, leafhopper transmitted [ 4 , 5 ], and also graft transmissible [ 6 , 7 , 8 ]. In addition to citrus species, the mollicute infects a wide range of non-rutaceous plant species such as carrot ( Daucus carota subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many of them are harmful, with deleterious effects on their hosts. Four papers in this Special Issue describe pathogen interactions (bacteria, fungi, oomycetes and parasitic nematodes) with various plants [ 7 , 8 , 9 , 10 ]. The work of Havrlentová et al [ 7 ] reported the consequences of artificial Fusarium infection on the quality of oat grain ( Avena sativa ).…”
mentioning
confidence: 99%
“…This disease is difficult to identify, as its symptomatology is not very different from that of other plant injuries caused by biotic and abiotic stresses. Sagouti et al [ 9 ] reported, in a comprehensive review, the recurrent problems caused by this disease in all regions where citrus grows and especially in those of the Mediterranean rim. Citrus stubborn disease is caused by Spiroplasma citri , a phloem-restricted bacterial pathogen of the Spiroplasmataceae family.…”
mentioning
confidence: 99%